2016
DOI: 10.1016/j.eurpsy.2016.01.1500
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of peripartum depressive symptoms among South Korean women – Preliminary data of a large prospective study

Abstract: ObjectiveThe aim of this study was to assess period prevalence and risk factors of peripartum depression in South Korean women.MethodsTwo thousand four hundred and forty-nine women in their first trimester of pregnancy were recruited, 1355 women were followed to the end of the study (1 month after delivery), 423 women are before the 1 month after delivery, 671 were dropped out. There were four time points of assessment – 12, 24, 36 weeks of gestation and 1 month after delivery. Depressive symptoms were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…A previous epidemiologic study in Korea showed that the prevalence of peripartum depression using the K-EPDS was found to be 18.8% in the 1st trimester, 12.9% in the 2nd trimester, 12.6% in the 3rd trimester, and 15.7% at 1 month after delivery. 48 This was very similar with our results, and psychiatric treatment would be recommended to help depressed pregnant women.…”
Section: Discussionsupporting
confidence: 91%
“…A previous epidemiologic study in Korea showed that the prevalence of peripartum depression using the K-EPDS was found to be 18.8% in the 1st trimester, 12.9% in the 2nd trimester, 12.6% in the 3rd trimester, and 15.7% at 1 month after delivery. 48 This was very similar with our results, and psychiatric treatment would be recommended to help depressed pregnant women.…”
Section: Discussionsupporting
confidence: 91%